The Alcohol Dehydrogenase Gene adhA in Corynebacterium glutamicum Is Subject to Carbon Catabolite Repression - Arndt, Annette (American Society for Microbiology (ASM), 2007)
Corynebacterium glutamicum has recently been shown to grow on ethanol as a carbon and energy source and to possess high alcohol dehydrogenase (ADH) activity when growing on this substrate and low ADH activity when growing on ethanol plus glucose or glucose alone. Here we identify the C. glutamicum ADH gene (adhA), analyze its transcriptional organization, and investigate the relevance of the transcriptional regulators of acetate metabolism RamA and RamB for adhA expression. Sequence analysis of adhA predicts a polypeptide of 345 amino acids showing up to 57% identity with zinc-dependent ADH enzymes of group I. Inactivation of the chromosomal adhA gene led to the inability to grow on ethanol and to the absence of ADH activity, indicating that only a single ethanol-oxidizing ADH enzyme is present in C. glutamicum. Transcriptional analysis revealed that the C. glutamicum adhA gene is monocistronic and that its expression is repressed in the presence of glucose and of acetate in the growth medium, i.e., that adhA expression is subject to catabolite repression. Further analyses revealed that RamA and RamB directly bind to the adhA promoter region, that RamA is essential for the expression of adhA, and that RamB exerts a negative control on adhA expression in the presence of glucose or acetate in the growth medium. However, since the glucose- and acetate-dependent down-regulation of adhA expression was only partially released in a RamB-deficient mutant, there might be an additional regulator involved in the catabolite repression of adhA.